Humanising academic staff development in higher education - Menon, K. (South African Journal of Higher Education, 2024)
This article focuses on academic staff development in higher education in South Africa. It emphasises the importance of locating academics within the broader racialised contexts and history of the country. Recognising the complexities of social academic exclusion in relation to academics working across the sector in diverse universities, the article argues that academic staff development programmes which provide formulaic interventions are far less likely to have a long term impact on the individual and the sector. The social and academic legacies of racial segregation continue to permeate the professional experiences of marginalised academics, the support they receive for their career aspirations, and the recognition (without acknowledgement) of institutional and systemic barriers to their success (Breetzke and Hedding 2018; Khunou 2018; Hlengwa 2019). The literature is replete with references to humanising pedagogies for students yet is overwhelmingly silent on the impact on the academic or aspirant academic. For transformation initiatives to have an impact, there is clearly a need to humanise the participants in academic development processes. What this implies is a full appreciation of the fact that academics enter universities with histories and experiences that inflect their work is central to the success of the transformation project. Thie article is premised on social justice which informs an understanding of transformation as the empowerment of academics through academic staff development programmes. Predicated on Sen’s “capability” approach, the article argues that academic development in the context of South Africa cannot afford to ignore the fractured history of the country.